El consumidor frente al Euro: El efecto ilusión monetaria a medio plazo - B. Álvarez Álvarez; Rodolfo Vázquez Casielles (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2007)
The present paper analyses the influence the introduction of the euro has had on the buying process developed by the consumer. The first aim pursued is to determine the effect of its coming into force on the formation of the reference prices estimated by the consumer. The second aim is to carry out a segmentation of the demand considering the easiness of adaptation of the new currency and the effects of the change on the buying process. Although other works have focused on analysing the immediate effects of the introduction of the euro, the view offered in our own research shows what the situation is like two years after the change of currency. The results are conclusive: the estimation of the reference prices still entails some difficulties, these being victims of an effect of monetary illusion. The adaptation process has not finished yet for a significant proportion of consumers, 48%, who face purchasing with important difficulties.
Keywords: 330; reference price; Euro; money illusion; segmentation